The digital humanities and islamic & Middle East studies - Muhanna, Elias (De Gruyter, 2016)
Over the past few decades, humanistic inquiry has been problematized and invigorated by the emergence of digital tools and methodologies. This collection of essays explores the state of the art in digital scholarship pertaining to Islamic & Middle Eastern studies, addressing areas such as digitization, visualization, text mining, databases, mapping, and e-publication.